Effect of Slag on the Strength and Shrinkage Properties of Metakaolin-Based Geopolymers - Jianghuai Zhan (Materials, 2022)
Metakaolin-based geopolymers possess excellent corrosion and high-temperature resistance, which are advantageous compared to ordinary Portland cement. The addition of slag in metakaolin-based geopolymers is a promising approach to improve their mechanical properties. Thus, this study investigated the effect of slag content on the strength and shrinkage properties of metakaolin-based geopolymers. Increasing the slag content and Na2O content was beneficial to the reaction of alkali-activated metakaolin-based geopolymers, thereby improving their compressive strength and density. After 56 days of aging, a maximum compressive strength of 86.1 MPa was achieved for a metakaolin-based geopolymer with a slag content of 50 mass%. When the Na2O content was 12%, the compressive strength of the metakaolin geopolymers with a slag content of 30% was 42.36% higher than those with a Na2O content of 8%. However, as the slag and alkali contents increased, the reaction rate of the metakaolin-based geopolymers increased, which significantly decreased the porosity, increased the shrinkage, and decreased the volumetric stability of the system. In this paper, in-depth study of the volume stability of alkali-activated metakaolin-based geopolymers plays an important role in further understanding, controlling, and utilizing the deformation behavior of geopolymers.